Exploring a state wildlife agency's account of contracted wildlife management and factors influencing contract use - Towry, Robert K., author; Cheng, Antony S., advisor; Reid, Robin S., committee member; Davis, Charles E., committee member; Remington, Thomas E., committee member (Colorado State University. Libraries, 2013)
State wildlife agencies are charged with trust responsibilities for wildlife resources. However the authorities of the agencies do not encompass all those needed to fulfill the trustee duties. This compels engagement of other government agencies, non-government entities and private parties in state wildlife management through incentives, collaborative management approaches and public engagement processes. However, details about the use of contracts related to collaborative management efforts and the relationships between the use of contract tools and state wildlife agency funding is not available. Accounting records and interviews with agency staff and contractors provide an account of collaborative management contracting which is not reported elsewhere. An in-depth case study of Colorado Division of Wildlife's (CDOW) use of contracts to accomplish wildlife management purposes was developed using accounting, appropriation and budget records and interviews with CDOW staff, state procurement staff and both non-profit and for profit contractors. A limited, interview only, case study of the Wyoming Game and Fish Department's (WGFD) use of wildlife management contracts was use to explore similarities or differences between two state wildlife agencies. CDOW's contract accounting records and legislative appropriations for fiscal years 1999 through 2010 used in the evaluation of the extent and changes in use. Twenty three interviews were conducted in Colorado and four with WGFD staff. The 12 fiscal years of contract accounting and appropriation records were explored for hypothesized relationships suggested from the government contracting literature. It was hypothesized that state wildlife agencies use of contracts differed from that described for other government agencies in the public administration literature in which contract use has been related to employee numbers or funding and shows increased use of contracts. The CDOW accounting records portray relatively stable levels of contract numbers. Service contracts, defined as all services and grant contracts, were not statistically related to total fiscal resources or staff levels. Total service contracts per fiscal year showed a small increase in numbers over the period however the expenditures on these contracts did not statistically differ. The number and value of contracts between CDOW and other government agencies or NGOs did not have statistically significant increases over the 12 year period. The value of grants contracts was found to be related to funds available. Further, grants and capital property acquisition spending was related to available fiscal resources. The informal semi-structured interviews were used to explored why and how extensively collaborative type contracts were used and to explore the benefits, difficulties and capacity needs related to their use. Contractor interviews focused on relationship with the state wildlife agency, difficulties in contracting with the agency and capacity issues related to contracting with either of the wildlife agencies. Interview content was analyzed using two approaches. One employed an a priori agency theory framework to code all interview transcripts. The second approach used a grounded theory based approach explore the themes related to collaborative contract use in the interview transcripts. An agency theory analysis was employed to provide insight into the agencies' contractor relationships and the interaction of agency theory with collaborative management contracts. The analysis of the procurement and wildlife agency principle-agent conflicts employed a shifting principle identity in which procurement/accounting staff and wildlife staff roles were switched to allow fuller characterization of the interview content. The conflict between the formal accountability based procurement procedures and wildlife staff's need for more flexibility is represented by the moral hazard coding characterized as goal conflicts. Wildlife agency staff identified adverse selection elements of performance and asymmetrical information most frequently in relation to contractors which is consistent with the emphasis placed on experience and relationships and the reported limited number of suitable contractors. Two main thematic elements emerged from the interviews as influencing the extent to which collaborative management contracts are used. The first is a systemic theme which identifies elements outside of the wildlife agency and includes legislation, budget, procurement policies and available contractors. The second is an institutional theme which includes constructed realities surrounding the relationships with and role of procurement processes, wildlife management norms and professionalism. A decision model is developed form informant provided content. The decision model and themes are supported by the procurement staff and contractors and accounting records. The results from the WGFD case support the results from the larger CDOW case suggesting they are characteristics shared by state wildlife management agencies.
Keywords: agency theory; collaborative management; contract use records; implementation capacity; institutional boundaries; state wildlife agencies